Mr. wrong number ebook - Painter, Lynn (Mr. Wrong Number, 2022)
Things get textual when a steamy message from a random wrong number turns into an anonymous relationship in this hilarious rom-com by Lynn Painter. Bad luck has always followed Olivia Marshall...or maybe she's just the screw-up her family thinks she is. But when a "What are you wearing?" text from a random wrong number turns into the hottest, most entertaining—albeit anonymous—relationship of her life, she thinks things might be on the upswing.... Colin Beck has always considered Olivia his best friend's annoying little sister, but when she moves in with them after one of her worst runs of luck, he realizes she's turned into an altogether different and sexier distraction. He's sure he can keep his distance, until the moment he discovers she's the irresistible Miss Misdial he's been sort of sexting for weeks—and now he has to decide whether to turn the heat up or ghost her before things get messy.